Electrochemical Synthesis of Lutetium (III) Hexacyanoferrate/poly(taurine) Modified Glassy Carbon Electrode for the Sensitive Detection of Sulfite in Tap Water. Issue 10 (1st January 2018) - Pandi, Karuppiah; Sivakumar, Mani; Chen, Shen-Ming; Sakthivel, Mani; Raghavi, Govindan; Chen, Tse-Wei; Liu, Yu-Chieh; Madhu, Rajesh
Abstract : The well-defined Lutetium (III) hexacyanoferrate microparticles were electrodeposited on poly(taurine) modified glassy carbon electrode (GCE), namely (LuHCF/poly(taurine)-GCE). The as-fabricated LuHCF/poly(taurine)-GCE possesses excellent electrochemical activities and high sensitivity toward the sensing of sulfite. The electrochemical oxidation of sulfite on LuHCF/poly(taurine)-GCE is studied by using Cyclic Voltammetry (CV), and Differential Pulse Voltammetry techniques (DPV). Remarkably, the reported modified electrode exhibits high sensitivity (448 μA mM −1 cm −2 ) and limit of detection (1.33 μM) toward the electrochemical oxidation of sulfite with superior selectivity and practicability.